Delicious Cyber Ghost: Using Pepper’s Ghost in Computer-Aided Design to Enhance Cantonese Morning Tea Education - Song Xu; Peng-Wei Hsiao; Chen Li; Jin-Yu Zhang (Engineering Proceedings)
Cantonese morning tea drinking is a cherished intangible cultural heritage in the Guangdong–Hong Kong–Macao Greater Bay Area in China and embodies Guangdong’s culinary tradition. In the digital era, innovative design techniques and digital technology have been applied to preserve and promote this tradition. To enhance heritage education, we designed an augmented reality device for Cantonese morning tea using Pepper’s Ghost technique. Employing field investigations, literature research, and experiments, we showcased Cantonese morning tea drinking. For further developments, affordable materials and professional photos are essential for constructing the model.